2017
DOI: 10.1111/bjh.14770
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of anti‐CD25 directed therapies as both immune modulators and targeted agents in cancer

Abstract: CD25 (also termed IL2RA) forms one component of the high-affinity heterotrimeric interleukin 2 (IL2) receptor on activated T cells. Its affinity for IL2 and cellular function are tightly regulated and vary in different cell types. The high frequency of CD25 on the surface of many different haematological tumour cells is now well established and, apart from its prognostic significance, CD25 may be present on leukaemic stem cells and enable oncogenic signalling pathways in leukaemic cells. Additionally, high CD2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 123 publications
1
71
0
2
Order By: Relevance
“…A highly immunosuppressive Treg subtype, expressing tumor-necrosis-factor-receptor 2 with activated NF-κB/p65 has been abundantly recognized in human ovarian cancers ( 52 ). In human hepatocellular carcinoma, the decreased survival rate was associated to a higher level of peripheral blood Tregs; similar observations have been reported in chronic lymphocytic leukemia (CLL) patients ( 53 ). However, controversial is the role of high Treg infiltration as a prognostic parameter in colorectal cancer ( 54 , 55 ).…”
Section: Nf-κb: a Forward Player Of Tregs Activity In Cancersupporting
confidence: 78%
“…A highly immunosuppressive Treg subtype, expressing tumor-necrosis-factor-receptor 2 with activated NF-κB/p65 has been abundantly recognized in human ovarian cancers ( 52 ). In human hepatocellular carcinoma, the decreased survival rate was associated to a higher level of peripheral blood Tregs; similar observations have been reported in chronic lymphocytic leukemia (CLL) patients ( 53 ). However, controversial is the role of high Treg infiltration as a prognostic parameter in colorectal cancer ( 54 , 55 ).…”
Section: Nf-κb: a Forward Player Of Tregs Activity In Cancersupporting
confidence: 78%
“…It has been reported that, in malignant CD4 + T cells derived from the CTCL, both of activated PI3K/AKT and MEK/ERK pathways contribute to mTORC1 activation, which appears to depend on the IL‐2‐induced γc/Jak signalling . IL‐2R has proven to be an attractive target for immune intervention and T cell‐directed therapies . To date, the IL‐2R target agents, such as daclizumab, basiliximab and denileukin diftitox, have demonstrated activity in diseases characterized by proliferation of activated T cells, but most of them are mainly used to protect against the rejection of certain organ transplants or cannot block IL‐2 signalling activated by intermediate affinity binding .…”
Section: Introductionmentioning
confidence: 99%
“…15 IL-2R has proven to be an attractive target for immune intervention and T cell-directed therapies. 16 To date, the IL-2R target agents, such as daclizumab, basiliximab and denileukin diftitox, have demonstrated activity in diseases characterized by proliferation of activated T cells, but most of them are mainly used to protect against the rejection of certain organ transplants or cannot block IL-2 signalling activated by intermediate affinity binding. [17][18][19] Importantly, daclizumab and basiliximab are two monoclonal antibodies to human IL-2Rα and there is no related small molecule compound targeting IL-2R on the market.…”
Section: Introductionmentioning
confidence: 99%
“…ADCT-301 is the first ADC against CD25, a receptor for IL-2 often found on hematological tumors that has a role in prognosis and oncogenesis in these malignancies [ 30 ]. This molecule is being studied in a phase I clinical trial in patients with relapsed or refractory HD and NHL ( NCT02432235 ).…”
Section: Antibody Drug Conjugatesmentioning
confidence: 99%